2020
DOI: 10.1111/aec.12976
|View full text |Cite
|
Sign up to set email alerts
|

Landscape monitoring reveals initial trends in occupancy and activity of bats in multiple‐use forests

Abstract: Biodiversity monitoring is recognised as a key action for ecologically sustainable land use, but there are few examples of landscape programmes. We outline the first five years of biodiversity monitoring focusing on insectivorous bats in low rainfall, multiple-use forests and woodlands of the Pilliga, Australia. Using ultrasonic sampling over multiple nights, both on-and off-tracks, we identify annual trends in bat activity and occupancy and environmental covariates. Trends differed depending on whether occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Unfortunately, there are few long‐term datasets available for bats to test these ideas (Law & Blakey, 2021). Recent analysis of trends in ultrasonic activity over 5 years in dry forests and woodlands of Australia have revealed that large variations in activity were negatively related to preceding wet winters rather than drought (Law et al, 2021). We suspect recruitment rather than adult survival to be the more sensitive population attribute affected by climate conditions in south‐eastern Australia, as was found for the trawling large‐footed myotis Myotis macropus (Law et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are few long‐term datasets available for bats to test these ideas (Law & Blakey, 2021). Recent analysis of trends in ultrasonic activity over 5 years in dry forests and woodlands of Australia have revealed that large variations in activity were negatively related to preceding wet winters rather than drought (Law et al, 2021). We suspect recruitment rather than adult survival to be the more sensitive population attribute affected by climate conditions in south‐eastern Australia, as was found for the trawling large‐footed myotis Myotis macropus (Law et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Only one species, Chalinolobus picatus (Gould), an edge-space forager, showed a negative response to the extent of recent burns (< 5 years); however, this species did not have a negative response to the extent of older burns. Further, the presence of C. picatus at the landscape scale was relatively stable over the 5 years (Law et al 2020) and its distribution across the Murray Mallee Region of southeastern Australia is not affected by burn extent (Senior et al 2021), suggesting that the negative effects of recent wildfire extent are local for this species. However, the distributions of several other species of bats in the Murray Mallee Region are negatively associated with burn extent (Additional file 4).…”
Section: Bat Responses To Burned Versus Unburned Sitesmentioning
confidence: 95%
“…The vagility of bats suggests that we should not make direct inferences or comparisons between the results of stand and landscape-scale studies. For example, while C. picatus activity is negatively related to the extent of recent burns at the stand scale, its presence across the landscape is relatively stable over time suggesting that the effects of fire are localized (Law et al 2020). Nonetheless, at the community scale, relationships between bat richness and wildfire extent, configuration, and pyrodiversity are relatively consistent across scales from ~3-30,000 ha .…”
Section: Bat Responses To Fire-prescribed Fire Versus Wildfirementioning
confidence: 99%
See 2 more Smart Citations